Identification of Auxiliary Biomarkers and Description of the Immune Microenvironmental Characteristics in Duchenne Muscular Dystrophy by Bioinformatical Analysis and Experiment - Han, Xu; Han, Jingzhe; Wang, Ning; Ji, Guang; Guo, Ruoyi; Li, Jing; Wu, Hongran; Ma, Shaojuan; Fang, Pingping; Song, Xueqin (Frontiers in Neuroscience, 2022)
Background: Duchenne muscular dystrophy (DMD) is a genetic muscle disorder characterized by progressive muscle wasting associated with persistent inflammation. This study was to identify potential diagnostic biomarkers and further characterize the immune microenvironment in DMD. Methods: Differentially expressed genes between DMD and normal tissues were identified based on Gene Expression Omnibus (GEO) datasets. Bioinformatical analysis was integrated to screen and identify diagnostic signatures of DMD which were further validated by qRT-PCR. Moreover, we applied single-sample gene-set enrichment analysis (ssGSEA) to characterize the proportion of tissue-infiltrating immune cells for assessing the inflammatory state of DMD. Results: 182 downregulated genes and 263 upregulated genes were identified in DMD. C3, SPP1, TMSB10, TYROBP were regarded as the diagnostic biomarkers and successfully validated by qRT-PCR. The infiltration of macrophage, CD4+, and CD8+ T cells was significantly higher in DMD compared to normal tissues, while activated B cell, CD56dim natural killer cell, and type 17 T helper cell (Th17) was lower. Additionally, the four diagnostic biomarkers were strongly associated with immune cells in DMD tissues. Conclusions: C3, SPP1, TMSB10, TYROBP were identified and validated as powerful diagnostic biomarkers of DMD. The immune cells infiltration in the muscle microenvironment might critically impact DMD development and occurrence.